Mediating Role of Creativity in Determining Innovation towards Competitive Advantage in Batik Creative Industry Indonesia - Wiwiek Harwiki; Mujiarto Mujiarto; Sri Hartini (International Journal of Supply Chain Management, 2020)
This study purposed to analyse the effects of (1) innovation on competitive advantage; (2) innovation on creativity, (3) creativity on competitive advantage The analysis used quantitative analysis, and as a descriptive analysis as well as an inferential statistics (SEM-PLS= Structural Equation Modelling-Partial Least Square). 55 respondents has been taken from the population of Batik Craft in East Java. This study proved the interesting findings that the diversity in samples appropriate with the diversity in population if eliminated: (1) product and process indicators of innovation; (2) novelty and elaboration indicators of creativity; and (3) competitive price, rarely found and not easy to be replaced indicators of competitive advantage. Therefore the rest of indicator is organizational innovation for innovation variable; resolution indocator for creativity variable; and 2 indicators for competitive advantage variable are: uniqueness and difficult to imitate. The result of probability value (Tstatistic) through bootstrapping of SmartPLS characteristic demonstrated the significance influence of (1) innovation on competitive advantage; (2) innovation on creativity, (3) creativity on competitive advantage. The result also found that the influence of mediation category of the relationship innovation to competitive advantage through creativity as mediator in complementary partial innovation on competitive advantage.